Clinical efficacy evaluation of 595‐nm pulsed dye lasers, microwave tissue coagulation, and liquid nitrogen cryotherapy in the treatment of verruca vulgaris in children. (12th April 2022) - Zhuang, Binyu; You, Yan; Zhang, Liang; Zhao, Fangqing; Guo, Yanping
Abstract: Objective: To evaluate the clinical efficacy and safety of 595‐nm pulsed dye laser in the treatment of verruca vulgaris in children and to compare the efficacy of this method against two other methods, microwave tissue coagulation and liquid nitrogen cryotherapy. Methods: A total of 90 children being treated in the dermatology outpatient department of our hospital from 2019 to 2021 were selected and divided into three groups: the treatment group A ( n = 30, treated with a 595‐nm pulsed dye laser), treatment group B ( n = 30, treated with microwave tissue coagulation), and treatment group C ( n = 30, treated with liquid nitrogen cryotherapy). All the patients in the treatment group A, treatment group B, and treatment group C were treated once every two weeks, with a maximum of six treatments. Results: The response rate of the treatment group A was 93.3%, which was higher than the 83.3% rate of treatment group B and the 66.7% rate of treatment group C. The average treatment times of the treatment group A (2.45 ± 1.10) were lower than group B (3.51 ± 0.98) and group C (4.63 ± 0.96). The adverse reaction rate in the treatment group A (16.7%) was significantly lower than that in treatment group B (56.7%) and treatment group C (63.3%). The differences were statistically significant (all p < 0.05). Conclusions: The 595‐nm pulsed dye laser is safe and seems to be the most effective treatment for verruca vulgaris in children. Further high‐level clinical trial is warranted to verify our results.